Durability Prediction of GFRP Rebar Based on Elastic Modulus Degradation - Tu, Jianwei; Xie, Hua; Gao, Kui; Li, Zhao; Zhang, Jiarui (Frontiers in Materials, 2019)
A conventional method to study the durability of Glass Fiber Reinforced Polymer (GFRP) rebars is to carry out tensile tests on the corroded GFRP bars. The degree of corrosion of the GFRP bars could be quantified based on the measured ultimate tensile strength and the calculated strength reduction. However, it is difficult to directly monitor the reduction in tensile strength of the GFRP rebars that are embedded in concrete; therefore, this method cannot be implemented in real engineering practices. This study presents the reduction in elastic modulus of the GFPR rebars by real-time monitoring of the strain of the GFRP rebars, and then establishes the degradation model of the elastic modulus for the GFRP rebars in an alkaline corrosion environment. Therefore, the relationship between tensile strength and elastic modulus of GFRP rebars is proposed and verified by the experimental data obtained from the literature. The results show that it is feasible to use the Arrhenius equation to simulate the degradation model of the elastic modulus of the GFRP rebars. Thus, the tensile strength of the GFPR rebars can be related to its elastic modulus. Using the proposed relationship, the durability of GFRP rebars can be predicted by real-time monitoring of the elastic modulus of the GFRP rebars.